STRATEGI PEMASARAN SATE KARAK DI WISATA RELIGI MAKAM SUNAN AMPEL SURABAYA - Maghfirotunnisa, Maghfirotunnisa; Al Baihaqi, Ariya Rifqi; Hikmah, Milta Fadzilatul (LPPM Universitas Nusa Mandiri, 2023)
Traditional culinary delights are not only souvenirs that decorate tourist destinations, but also influence the image and attraction of tourists towards a tourist location. In this context, one of the Karak satay stalls in the Sunan Ampel Tomb area, Surabaya, was able to survive and continue to exist with its authentic taste amidst increasingly fierce business competition. This article was written to outline alternative marketing strategies in facing intense competition in the culinary industry by taking the example of the satay karak stall at the Sunan Ampel Tomb religious tourism in Surabaya. Researchers try to analyze using a qualitative approach method using literature studies obtained from various books, articles, journals and online news. This results in the right marketing strategy for Sate Karak involving several important aspects such as the marketing mix, identifying target markets, collaboration with business actors, and culinary participation in special events.